Thirty Years After Marr's Vision: Levels of Analysis in Cognitive Science. (9th March 2015) - Peebles, David; Cooper, Richard P.
Abstract Thirty years after the publication of Marr's seminal book Vision (Marr, 1982) the papers in this topic consider the contemporary status of his influential conception of three distinct levels of analysis for information‐processing systems, and in particular the role of the algorithmic and representational level with its cognitive‐level concepts. This level has (either implicitly or explicitly) been downplayed or eliminated both by reductionist neuroscience approaches from below that seek to account for behavior from the implementation level and by Bayesian approaches from above that seek to account for behavior in purely computational‐level terms.